Bibliometric analysis of rheumatic immune related adverse events associated with immune checkpoint inhibitors - Zeng, Li; Ma, Gang; Chen, Kai; Zhou, Qiao (Frontiers in Immunology, 2023)
Background: Immune checkpoint inhibitors (ICIs) has emerged as a popular cancer treatment approach. However, non-specific activation of T cells by ICIs can lead to immune-related adverse events (irAEs), including specific rheumatic manifestations.The study aimed to explore the current trend of ICIs associated rheumatic irAEs and summarize the knowledge structure through bibliometric methods.Methods: The Web of Science Core Collection database (WoSCC) was selected for retrieving literature on ICIs associated rheumatic irAEs. To evaluate contributions from different countries/regions, institutions, journals, and authors, bibliometric analysis software, including VOSviewer and CiteSpace, as well as bibliometric online platforms, were utilized to construct and visualize bibliometric networks. Through the systematic review of this knowledge domain, future research directions were determined.Results: In This study, a total of 803 publications on ICIs-associated rheumatic irAEs were included for analysis. The distribution of these publications revealed two distinct growth phases: a stable phase between 2007 to 2015 followed by rapid growth from 2016 to 2020. The United States emerged as the top contributor in terms of publications, citations, and h-index, with the majority of leading institutions and funding agencies located there. Apart from government funding, pharmaceutical companies such as Bristol Myers Squibb and Merck Company also play a significant role in drug development and research. Analysis of keywords and citation bursts indicated that the initial burst was related to "monoclonal antibody," "anti-CLTA4 antibody," and "melanoma". This was followed by a rise in interest related to "sarcoidosis," "safety," "inflammatory arthritis," and "preexisting autoimmune." Conclusion: This study summarized the global research trends concerning ICIs associated rheumatic irAEs. The findings can provide valuable insights into the current understanding of rheumatic irAEs, highlight the research trend and developments in the field. Future efforts should focus on developing classification criteria and guidelines, conducting prospective studies, investigating the mechanisms involved, and identifying biomarkers for prediction and monitoring of these events.